TSC22D2 identified as a candidate susceptibility gene of multi-cancer pedigree using genome-wide linkage analysis and whole-exome sequencing. (24th May 2019) - Xiao, Lan; Wei, Fang; Liang, Fang; Li, Qiao; Deng, Hao; Tan, Shiming; Chen, Shuai; Xiong, Fang; Guo, Can; Liao, Qianjin; Li, Xiayu; Zhang, Wenling; et al.
Abstract: Cancer is a complex disease, which may involve multiple tumor susceptibility genes that mediate the occurrence and development of tumor molecular events. This study aimed to identify new genetic loci using genome-wide linkage analysis and whole-exome sequencing in a rare, large multi-cancer pedigree recently found in China. We performed high-throughput single-nucleotide polymorphism (SNP) array and linkage analyses of 24 core members of this pedigree and found that the disease susceptibility locus in the multi-cancer pedigree was mapped to chromosome 3q24-26. We also used microsatellites to further validate the results of the SNP locus linkage analysis. Furthermore, we sequenced the whole exome of three members in this pedigree and identified a novel mutant of transforming growth factor β stimulated clone 22 domain family, member 2 ( TSC22D2, c.-91T-C) cosegregated with the cancer phenotype. This change was at a highly conserved position, and the exome results were validated using linkage analysis. Moreover, we found the histone H4 transcription factor ( HINFP ) binds to the promoter region of TSC22D2 and may regulate its transcription. In conclusion, our findings are of great significance to the early pathogenesis of tumors and contribute to the search for molecular targets for the early prevention and treatment of tumors. Abstract : A rare, large multi-cancer pedigree was analyzed in China. The disease susceptibility locus was mapped to chromosome 3q24-26 using high-throughput single-nucleotide polymorphism array and linkage analysis. A novel TSC22D2 mutant (c.-91T-C) was cosegregated with the tumor phenotype using exome sequencing.